Effect of Psychoeducational Programme on Stress Level and Coping Responses Among College Students - Chai, Ming Sing (2005)
This study consisted of two parts. In the first part of the study, the descriptive correlational research method was used to explore the different ways of coping and level of stress among college students at two different points of time in a semester. Apart from that, the relationship between these two variables as well as their differences in terms of sex, level, year, and course of study were also explored. In the second part of the study, pretest-post test design was used. A pre-test was administered to all subjects of the study to measure the level of stress before treatment condition was introduced. They were measured again after the treatment was given to determine the effect of such a psychoeducational programme on the level of stress. The treatment condition was in the form of six group sessions, 50 minutes each, every week conducted by the researcher.The overall number of subjects who participated and completed all questionnaires during week 3 was 395. The size of the sample used in the data analysis for the experimental and control group was 32 each. Results showed that the majority of TAR College students experience moderate to high levels of stress at the beginning of an academic semester. There was no significant increase in the level of stress experienced by students from week 3 to week 11. The level of stress among college students did not differ in terms of sex, level, year, and course of study. The most frequently used coping response among students was positive reinterpretation and growth. Male and female students differed in the use of various coping responses. Certain ways of coping were related to the level of stress among students. Experimental study showed that the psychoeducational programme had a positive effect on the level of stress among students. The decrease in the level of stress was greater among subjects who had undergone group sessions as compared to those who had not in the control group. As a conclusion, the study has provided some insights to the effectiveness of using psychoeducational programme to help students cope with their stress, the level of stress among students, and their coping responses used by college students. This information will be helpful to student counsellors in helping students to cope with their stress.